Annealing effects on photoresist films' mechanical and chemical resistance - Avellaneda, Manuel (2023)
Nowadays, photoresist-based films are used by photolithography techniques for the fabrication of micro/nanodevices in the modern nanotechnology industry. The impact of thermal-induced polymerization on the mechanical resistance of these materials is critical for improving both the mechanical and the chemical performance. In this work, we present a systematic study of the annealing effects on the mechanical resistance (thermally-induced material hardening) of MICROPOSIT™ photoresist films. The mechanical properties were studied by depth-sensing nanoindentation technique using an atomic force microscope. Results show the films' plastic strain susceptibility decreases as the annealing temperature increases, implying an improvement of their mechanical resistance by thermal-induced polymerization. Strain energy dissipation coefficients decreased from 0.725 up to 0.525 as the annealing temperature was increased from 60 up to 200 °C, demonstrating this point. Indentation hardness results were consistent with this behavior, observing an increase from 0.12 up to 0.23 [GPa] for the highest annealing temperature. Annealing-induced hardening seems to be correlated with the films' resistance to wet chemical etching, observing higher chemical resistance for higher annealing temperatures. The observed increase of the mechanical and chemical resistance of the photoresists with annealing becomes of great importance for their application in the development of novel micro and nanostructures.